Allelic variations in GA20ox3 regulate fruit length and seed germination timing for high-altitude adaptation in Arabidopsis thaliana - Xuemeng Gao; Shangling Lou; Yu Han; Yudan Zheng; Xiaoqin Feng; Han Zhang; Xuejing Liu; Jing Hou; Yingjun Yao; Yan Song; Meng Liu; Shaobo Gu; et al. (Nature Communications)
Abstract Altitude significantly affects both fruit length (FL) and seed germination timing (SGT) in plants. Alpine plants often require prolonged chilling to enhance seed germination rates, yet the molecular mechanisms underlying these adaptations remain largely unexplored. In this study, we have identified the gibberellin biosynthesis gene GA20ox3 as a key regulator of FL and SGT in Arabidopsis thaliana. Our findings demonstrate that DELLA proteins form a negative feedback loop by interacting with the transcription factor DNA-BINDING ONE ZINC FINGER6 (DOF6), which directly binds to the GA20ox3 promoter. Allelic variations in the GA20ox3 promoter of one alpine ecotype influence the binding affinity of DOF6, leading to variations in both FL and SGT. The geographical distribution of the GA20ox3 promoter alleles, corresponding well to different altitudes and temperatures, underscores the significant role of such variation in the A. thaliana’s adaptation to the varied habitats, especially concerning seed germination timing. Our results reveal a cold-mediated gibberellin signaling mechanism that controls both FL and SGT, thereby optimizing reproductive success in varied environments.